STUDI SIFAT FISIK TANAH PADA KEBUN KARET DAN KELAPA SAWIT DI DESA RASAN KECAMATAN NGABANG KABUPATEN LANDAK - Riduan Riduan; Junaidi Junaidi; Rita Hayati (Fakultas Pertanian Universitas Tanjungpura, 2021)
This study aimed to compare the physical properties of soil on rubber and oil palm plantation in the village of the District Rasan Ngabang Porcupine District. Observation point soil samples taken at rubber plantations and palm oil to a depth of 0-30 cm and 30-60 cm. Parameter observations used in this study consists of the characteristic physical properties of the soil that is the color of the soil, soil structure, soil texture, bulk density soil, the water content of field capacity, soil porosity, permeability, stability of soil aggregates, content of organic C, N-total , C / N ratio, and soil reaction (pH).The observation of the color of the soil in the field on rubber plantations and palm oil is known that, there are some differences and similarities at each point of observation well was at a depth of 0-30 cm and 30-60 cm. The structure of a rubber garden soil to a depth of 0-30 cm and 30-60 cm blocky rounded grains (granular) while in the oil palm plantation with a depth of 0-30 cm and 30-60 cm soil structure is blocky angular. While the texture of the soil at a depth of 0-30 cm rubber plantations and 30-60 cm termaksuk sandy clay loam and clayey loam soil texture while the oil palm plantation with a depth of 0-30 cm and 30-60 cm including sandy clay loam, clay and loam clayey.T test results on soil bulk density rubber plantations and palm oil at a depth of 0-30 cm showed significantly different while the depth of 30-60 cm are not significantly different, while the t-test, field capacity moisture content in the rubber plantations and palm oil at a depth of 0-30 cm showed significantly different at a depth of 30-60 cm while not significantly different. The results of the t test soil porosity rubber plantations and palm oil at a depth of 0-30 cm and 30-60 cm are not significantly different. While the t-test, soil permeability in rubber plantations and palm oil to a depth of 0-30 cm and 30-60 cm showed no significant difference.Soil aggregate stability was higher in oil palm plantations over rubber either the depth of 0-30 cm and 30-60 cm. While the results of the analysis of organic materials in the rubber plantations and palm oil is low to very low both at a depth of 0-30 cm and 30-60 cm, N-total is low to very low, and C / N ratio is low and soil reaction ( pH) sour to very sour.